PENDIDIKAN MELAWAN KORUPTOR ZAMAN NOW - Bimayu, Warih (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Corruptors are the biggest dilemma present in Indonesian society today, as if their actions are ordinary but have tremendous consequences, especially for this nation and country. As if everyone was lulled by assuming the corruptor's actions were said to be reasonable and increasingly rampant. Indonesia is classified by Transparency International institutions including the most corrupt country in the world. The purpose of this research is to respond to teachers and students through their knowledge to explore various information about the role of the world of education in dealing with corrupt practices in Indonesia. Information and research data came from teachers and students of SMAN 1 Sungai Rotan and collected through direct interview techniques aimed at knowing the extent of the perceptions of teachers and students about the role of education in corruptors that occurred in Indonesia and related to the latest reality and information. The results of this study indicate the perceptions of teachers and students of corruptors is that corruptors must be eradicated to the root and the government immediately makes policies regarding charged curriculum about the impact and influence of corruptors on the nation and state. So that education is needed about the knowledge of corruptors in schools from the elementary, secondary and even tertiary levels so that future generations do not follow in the footsteps of corruptors who always harm the money and assets of the country due to policies of officials who blame their positions